Identification of genetic markers of resistance to echinocandins, azoles and 5-fluorocytosine in Candida glabrata by next-generation sequencing: a feasibility study. (September 2017) - Biswas, C.; Chen, S.C.-A.; Halliday, C.; Kennedy, K.; Playford, E.G.; Marriott, D.J.; Slavin, M.A.; Sorrell, T.C.; Sintchenko, V.
Abstract: Objectives: Multi-antifungal drug resistance in Candida glabrata is increasing. We examined the feasibility of next-generation sequencing (NGS) to investigate the presence of antifungal drug resistance markers in C. glabrata . Methods: The antifungal susceptibility of 12 clinical isolates and one ATCC strain of C. glabrata was determined using the Sensititre YeastOne ® YO10 assay. These included three isolate pairs where the second isolate of each pair had developed a rise in drug MICs. Single nucleotide polymorphisms (SNPs) in genes known to be linked to echinocandin, azole and 5-fluorocytosine resistance were analysed in all isolates through NGS. Results: High-quality non-synonymous SNPs in antifungal resistance genes such as FKS1, FKS2, CgCDR1, CgPDR1 and FCY2 were identified. For two of three isolate pairs, there was a >60-fold rise in MICs to all echinocandins in the second isolate from each pair; one echinocandin-resistant isolate harboured a mutation in FKS1 (S629P) and the other in FKS2 (S663P). Of the third pair, both the 5-fluorocytosine-susceptible, and resistant isolates had a mutation in FCY2 (A237T). SNPs in CgPDR1 were found in pan-azole-resistant isolates. SNPs in other genes linked to azole resistance ( CgCDR1, ERG9 and CgFLR1 ) were present in both azole-susceptible and azole-resistant isolates. SNPs were also identified in Candida adhesin genes EPA1, EPA6, PWP2 and PWP5 but their presence was not associated with higher drug MICs. Conclusions: Genome-wide analysis of antifungal resistance markers was feasible and simultaneously revealed mutation patterns of genes implicated in resistance to different antifungal drug classes.